Recovery of cycling gross efficiency after time-trial exercise - Groot, S.; van de Westelaken, L. H. J.; Noordhof, D. A.; Levels, K.; de Koning, J. J. (International Journal of Sports Physiology and Performance, 2018)
Background: Research has shown that gross efficiency (GE) declines during high-intensity exercise, but the time course of recovery of GE after high-intensity exercise has not yet been investigated. Purpose: To determine the time course of the recovery of GE after time trials (TTs) of different lengths. Methods: Nineteen trained male cyclists participated in this study. Before and after TTs of 2000 and 20,000 m, subjects performed submaximal exercise at 55% of the power output attained at maximal oxygen uptake (PVO2max). The postmeasurement continued until 30 min after the end of the TT, during which GE was determined over 3-min intervals. The magnitude-based-inferences approach was used for statistical analysis. Results: GE decreased substantially during the 2000-m and 20,000-m TTs (-11.8% [3.6%] and -6.2% [4.0%], respectively). A most likely and very likely recovery of GE was found during the first half of the submaximal exercise bout performed after the 2000-m, with only a possible increase in GE during the first part of the submaximal exercise bout performed after the 20,000-m. After both distances, GE did not fully recover to the initial pre-TT values, as the difference between the pre-TT value and average GE value of minutes 26-29 was still most likely negative for both the 2000- and 20,000-m (-6.1% [2.8%] and -7.0% [4.5%], respectively). Conclusions: It is impossible to fully recover GE after TTs of 2000- or 20,000-m during 30 min of submaximal cycling exercise performed at an intensity of 55% PVO2max.